Effect of Thermomechanical Treatments on Microstructure, Phase Composition, Vickers Microhardness, and Young’s Modulus of Ti-xNb-5Mo Alloys for Biomedical Applications - Cardoso, Giovana Collombaro [UNESP]; Buzalaf, Marília Afonso Rabelo; Correa, Diego Rafael Nespeque [UNESP]; Grandini, Carlos Roberto [UNESP] (MDPI, 2022)
The development of new β-Ti alloys has been extensively studied in the medical field in recent times due to their more suitable mechanical properties, such as a relatively low Young’s modulus. This paper analyzes the influence of heat treatments (homogenization and annealing) and hot rolling on the microstructure, phase composition, and some mechanical properties of ternary alloys of the Ti-xNb-5Mo system, with an amount of Nb varying between 0 and 30 wt%. The samples are produced by argon arc melting. After melting, the samples are homogenized at 1000◦ C for 24 h and are hot rolled and annealed at 1000◦ C for 6 h with slow cooling. Structural and microstructural analyses are made using X-ray diffraction and optical and scanning electron microscopy. Mechanical properties are evaluated by Vickers microhardness and Young’s modulus. The amount of β phase increases after heat treatment and reduces after hot rolling. The microhardness and Young’s modulus of all heat-treated samples decrease when compared with the hot rolled ones. Some samples exhibit atypical Young’s modulus and microhardness values, such as 515 HV for the as-cast Ti-10Nb-5Mo sample, indicating the possible presence of ω phase in the microstructure. The Ti-30Nb-5Mo sample suffers less variation in its phase composition with thermomechanical treatments due to the β-stabilizing effect of the alloying elements. The studied mechanical properties indicate that the annealed Ti-30Nb-5Mo sample has potential for biomedical applications, exhibiting a Young’s modulus value of 69 GPa and a microhardness of 236 HV.
Keywords: biomaterial; microhardness; microstructure; phase composition; thermomechanical treatments; Ti alloys; Young’s modulus